Nutritional supplements - Boosting your performance - Hamilton, A. (Peak Performance, 2004)
Natural immunity: Foods and supplements to build and maintain it Essential fats: The answer to most athletes` prayers -helping to conserve carbohydrate while shedding fat Iron deficiency: Much more prevalent than you imagined and posing particular risks for athletes Antioxidant vitamins: Can they do athletes more harm than good? Chromium: Just how ergogenic is this trace element - and how much is too much? Conjugated Linoleic Acid: Is it really a magic route to fat loss and a healthy old age? ALC and ALA: Could they combine to form the Elixir of Life? What the scientists say: Why power trainers need extra protein - Re-think on zinc - GACIK - is it even better than creatine? - Sodium bicarbonate and sprint performance